Merajut Kembali Toleransi di Era Post-Truth: Respon Al-Qur’an Terhadap Kebebasan Beragama - Lufaefi (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
The era of post-truth known as the era of placing truth in second place is considered a challenge of the modern world. This position is also often used in issues of tolerance and religious freedom in plural societies such as Indonesia. Religious tolerance is considered right by someone when another group follows his belief. This results in weak freedom to embrace religion and beliefs. The Koran responds to the problem of religious freedom. Islam through the Prophet Muhammad himself taught his people not to force on matters of faith, even to the closest people. The Koran still believes strongly that only Islam is the true religion. But do not consider any other religions. The essence of religion is the same, realizing Allah and doing good. Islam refuses coercion in religion, for any reason. Islam frees people to choose other beliefs, even though it is believed that only Islam is the true religion.